Proses Pemilihan Pemimpin dalam Alquran Analisis Kontekstualis Pemilu di Indonesia 2024 - Hibatullah, Alif; Bakar, Abu (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
The replacement of leaders often sparks conflict, involves political funding loss of lives, and enters the list of issues faced. The reinterpretation of Article 169 letter q of Law number 7 of 2017 has become a political dynasty issue in Indonesia. Choosing leaders, which should ideally be a sacred moment and a hope for a better life for society, has unfortunately turned into a moment of contention. As members of the Muslim community, one certainly hopes that the Quran will become the book that provides answers to the challenges of our time. The method employed in this research is qualitative with a library research approach. This study identifies three selection processes: First, Allah chooses leaders directly, as stated in Surah ql-Baqarah verse 30 and Surah Sad verse 26. This selection is the prerogative of Allah, untainted by interference and irrevocable in its decision. Second, leaders are chosen by the Prophet, as mentioned in Surah ql-Baqarah 246-247. Society can consult to delegate authority to the Prophet to appoint a leader among them. This method of selecting leaders is suitable for use in Indonesia, as it minimizes fraud while reducing societal conflicts. Even though there is currently no figure like the Prophet to guide leadership, this role can be represented by the people’s representatives. Third, leaders are chosen by the preceding leader, based on the evidence in Surah Yusuf verses 54-56. The Egyptian King, impressed by Prophet Yusuf’s linguistic abilities, interpretation skills, and wealth management, granted his wish to become the treasurer, as requested by Prophet Yusuf. These verses indicate the characteristics of a competent leader who shoulders responsibilities according to their capacity.